A novel and accurate technique of photographic wound measurement - Shetty, Rahul; Sreekar, H.; Lamba, Shashank; Gupta, Ashish Kumar (Indian Journal of Plastic Surgery, 2012)
Context: Wound measurement is an important aspect of wound management. Though there are many techniques to measure wounds, most of them are either cumbersome or too expensive. Aims: To introduce a simple and accurate technique by which wounds can be accurately measured. Settings and Design: This is a comparative study of 10 patients whose wounds were measured by three techniques, i.e. ruler, graph and our technique. Materials and Methods: The graph method was taken as the control measurement. The extent of deviation in wound measurements with our method was compared with the standard technique. The statistical analysis used was ANOVA. Results: The ruler method was highly inaccurate and overestimated the wound size by nearly 50%. Our technique remained consistent and accurate with the percentage of over or underestimation being 2-4% in comparison with the graph method. Conclusions: This technique is simple and accurate and is an inexpensive and non-invasive method to accurately measure wounds.
Keywords: Digital planimetry; photography; wound measurement